Interaction Design For Implementation Multi-Window on Smartphone - Samuel Aristides; Fetty Fitriyanti Lubis (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2023)
The use of smartphones varies from person to person, and one of the uses that requires attention is multitasking using a smartphone. Multitasking is usually done on computers, but the increase in smartphones’ screen size and RAM capacity makes it an option for multitasking. The implementation of multitasking on smartphones still has weaknesses, and this final project aims to create an interaction design that overcomes these weaknesses. The method used is user-centered design with problem analysis through questionnaires and current implementation analysis, followed by determining needs, followed by creating low fidelity and high fidelity designs, and finally testing those designs. Two iterations of the design resulted in a final design that has a SUS score of 91 (Grade A), an ease of use score that is not lower than 6.3 out of 7, a task completion rate of 100%, and icons that are almost entirely easy to find with a time-to-locate time of 0-5 seconds. The final design can be implemented on Android, but implementation on iOS needs to wait for its software to support the proposed solution.